Features of Inanimate Subject in Japanese, English and Ukrainian - Фурманова, П. (Київський національний університет імені Тараса Шевченка, 2022)
The article summarizes the main approaches to the problem of inanimate subject in Japanese. While English has a strong tendency to use inanimate subject on a daily basis, Japanese language has a lot of restrictions for this type of construction. As these restrictions seem to appear both in subjects and predicates of the sentences, the two approaches - nominal and verbal - were elaborated in order to account for the phenomena. Nominal approach accounts for the nouns, that tend to appear in the subject or object position, while verbal approach tries to find out which verbs can be used in the sentences with an inanimate subject. This article outlines the nominal approach and explains two theories that were elaborated in Japanese studies. The first theory developed by T. Tsunoda adopts referential hierarchy of Silverstein and states that although personal pronouns and nouns that indicate animate objects have a stronger tendency to become a subject of the sentence, there is a hierarchy between the nouns that name inanimate objects. For example, the nouns that indicate natural forces are more likely to become the subject of the sentence than nouns that indicate abstract notions and territory names. The second theory developed by S. Saito adopts the empathy hierarchy (hierarchy of the positions) of S. Kuno in order to account for the extending acceptance of the sentences with inanimate subject that include auxiliary verb ‘kureru'. The theory states that ‘kureru' in such types of sentences manages to balance empathy on the non-subject participant (which is an animated entity) rather than the subject, that results into an acceptance of the type of sentences. The article also suggests that there are some similarities in the way Ukrainian and Japanese speakers tend to translate English sentences that have an inanimate subject. The article also points out the necessity for Ukrainian studies to develop its own approach to the sentences with inanimate subject, because it seems that Ukrainian language has its own restrictions on such sentences.

У статті розглянуто явище агентивного неживого підмета в японській, англійській та українській мовах. Визначено основні два підходи до розв'язання питання агентивного неживого підмета в японській мові: іменниковий та дієслівний, а також детально охарактеризовано іменниковий підхід. Розглянуто теорії про референційну ієрархію та ієрархію позицій.
Особливості агентивного неживого підметав японській, англійській та українській мовах
Keywords: inanimate subject; referential hierarchy; hierarchy of the posi¬tions; empathy hierarchy; personification; empathy; агентивний неживий підмет; референційна ієрархія; ієрархія позицій; персоніфікація; емпатія